High-efficiency solid-phase microextraction performance of polypyrrole enhanced titania nanoparticles for sensitive determination of polar chlorophenols and triclosan in environmental water samples. Issue 46 (25th August 2021) - Ma, Mingguang; Wei, Yunxia; Wei, Huijuan; Liu, Xianyu; Liu, Haixia
Abstract : A PPy/TiO2 nanocomposite coating was fabricated by direct electropolymerization of pyrrole on annealed TiO2 nanoparticles and evaluated as a novel direct immersion solid phase microextraction fiber coating for the extraction of trace pollutants in water. Abstract : In this work, a polypyrrole (PPy)/TiO2 nanocomposite coating was fabricated by the direct electropolymerization of pyrrole on annealed TiO2 nanoparticles and evaluated as a novel direct immersion solid phase microextraction (DI-SPME) fiber coating for extraction of trace amounts of pollutants in environmental water samples. The functionalized fiber is mechanically and chemically stable, and can be easily prepared in a highly reproducible manner. The effects of the pyrrole monomer concentration, polymerization voltage and polymerization time on the fiber were discussed. Surface morphological and compositional analyses revealed that the composite coating of nano polypyrrole and titanium dioxide nanoparticles (TiO2 NPs ) uniformly doped the Ti substrate. The as-fabricated fiber exhibited good extraction capability for phenolic compounds in combination with high performance liquid chromatography-UV detection (HPLC-UV). At the optimum SPME conditions, the calibration curves were linear ( R 2 ≥ 0.9965). LODs and LOQs of less than 0.026 μg L −1 and 0.09 μg L −1, respectively, were achieved, and RSDs were in the range 3.5–7.2%. The results obtained in this work suggest that PPy/TiO2 is a promising coating material for future applications of SPME and related sample preparation techniques.